DOI: 10.31274/rtd-180813-15569
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing malformation of the leg bones of growing chicks

Abstract: The quality of this reproduction is dependent upon the quality of the copy submitted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleed-through, substandard margins, and improper alignment can adversely affect reproduction. In the unlikely event that the author did not send a complete manuscript and there are missing pages, these will be noted. Also, if unauthorized copyright material had to be removed, a note will indicate the deletion. UMI UMI Microform DP13377

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…The significant negative correlation found between perosis and organic phosphorus helps to explain why the correlation coefficient between perosis and phosphorus in this study, and that reported by Milby (1933) between slipped tendon and phosphorus leave so much variation unaccounted for.…”
Section: Results Of the Statistical Analysismentioning
confidence: 48%
See 3 more Smart Citations
“…The significant negative correlation found between perosis and organic phosphorus helps to explain why the correlation coefficient between perosis and phosphorus in this study, and that reported by Milby (1933) between slipped tendon and phosphorus leave so much variation unaccounted for.…”
Section: Results Of the Statistical Analysismentioning
confidence: 48%
“…Titus (1932) concluded that rice bran contains a factor which is necessary for the normal development of bone in the case of the chicken. Milby (1933) found high correlation between slipped tendon and total phosphorus content of the diet. Insko, Sowell and Lyons (1934) reported that widening the Ca:P ratio with its accompanying increase of calcium in the diet from 0.4:1 to 3.1:1 did not increase the percentage of slipped tendon.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…These results have been discussed by Milby (1934). SUMMARY It is clear that there is no significant difference in the ash content of femurs, tibiae, or metatarsi of chicks on various rations which are afflicted with slipped tendon and the ash content of the corresponding bones of chicks on a control ration at the same age.…”
mentioning
confidence: 76%